A Genetic Network Underlying Rhizome Development in Oryza longistaminata - Li, Wenfei; Zhang, Shilai; Huang, Guangfu; Huang, Liyu; Zhang, Jing; Li, Zheng; Hu, Fengyi (Frontiers in Plant Science, 2022)
The rhizome is an important organ through which many perennial plants are able to propagate vegetatively. Its ecological role has been thoroughly studied on many grass species while the underlying genetic basis is mainly investigated using a wild rhizomatous rice species—Oryza longistaminata. Previous studies have revealed that the rhizome trait in O. longistaminata is jointly controlled by multiple loci, yet how these loci interact with each other remains elusive. Here, an F2 population derived from O. sativa (RD23) and O. longistaminata was used to map loci that affect rhizome-related traits. We identified 13 major-effect loci that may jointly control rhizomatousness in O. longistaminata and a total of 51 quantitative trait loci (QTLs) were identified to affect rhizome abundance. Notably, some of these loci were found to have effects on more than one rhizome-related trait. For each trait, a genetic network was constructed according to genetic expectations of the identified loci. Furthermore, to gain an overview of the genetic regulation on rhizome development, a comprehensive network integrating all these individual networks was assembled. This network consists of three subnetworks that control different aspects of rhizome expression. Judging from the nodes’ role in the network and their corresponding traits, we speculated that qRHZ-3-1, qRHZ-4, qRHI-2, qRHI-5 are the key loci for rhizome development. Functional verification using rhizome-free recombinant inbred lines (RILs) suggested that qRHI-2 and qRHI-5, two multi-trait controlling loci which appeared to be critical in our network analyses, are likely both needed for rhizome formation. Our results provide more insights into the genetic basis of rhizome development and may facilitate the identification of key rhizome-related genes.